2020
DOI: 10.1002/jbt.22574
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Syringic acid modulates molecular marker–involved cell proliferation, survival, apoptosis, inflammation, and angiogenesis in DMBA‐induced oral squamous cell carcinoma in Syrian hamsters

Abstract: Despite, different medicinal phyto compounds giving an inexhaustible variety of anticancer drugs, potent signalling mechanism of leads  the key successes of anticancer agent, anti‐inflammatory, induction of apoptosis, and antiangiogenic. The current study was conducted to estimate the effect of syringic acid (SA) on tumor necrosis factor‐α (TNF‐α)‐mediated nuclear factor‐κB (NF‐κB) signaling pathways, inducing apoptosis and angiogenic signaling pathways in a hamster model by preneoplastic stages, histological,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…One of the previous studies showed that SRA inhibits proliferation and apoptotic induction in hamster buccal pouch carcinogenesis. [ 23,29,30 ] Karthik et al . [ 31 ] studied SRA‐induced apoptosis which is confirmed by nuclear morphology (PI staining assay) which showed condensed nuclei and fragmented apoptotic bodies in adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…One of the previous studies showed that SRA inhibits proliferation and apoptotic induction in hamster buccal pouch carcinogenesis. [ 23,29,30 ] Karthik et al . [ 31 ] studied SRA‐induced apoptosis which is confirmed by nuclear morphology (PI staining assay) which showed condensed nuclei and fragmented apoptotic bodies in adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The active compound 4-hydroxy-3,5-dimethoxybenzoic acid is derived from Euterpe oleracea and Rhus javanica extract, and inhibits colorectal cancer and oral squamous cell carcinoma [ 46 , 47 ]. Syringic acid (0.2 and 1 mM) prevented UVB (0.2 J/cm 2 )-induced skin papilloma and tumors in SKH-1 hairless mice [ 48 ].…”
Section: Akt and Related Signaling Pathway Inhibitors For Skin Canmentioning
confidence: 99%
“…Chemotherapeutic compounds that target rapidly dividing cells are commonly used in anticancer therapy. Regrettably, this technique has a severe side effect, as it affects normal, fast‐dividing cells including hair follicles and epithelial cells in the digestive system (Pandey & Khan, 2021; Periyannan et al, 2020; Thakur et al, 2020). Furthermore, one of the exacerbating factors is that many cancer cells gain resistance to traditional treatments over time.…”
Section: Introductionmentioning
confidence: 99%